Conflicts Of Land Confiscationis In Sogo Village: Community Versus PT.Bukit Bintang Sawit (WILMAR) - irwan, Irwan; Afrizal, Afrizal; Zusmelia, Zusmelia; Maihasni, Maihasni (Universitas Negeri Semarang, 2018)
Conflicts of land confiscationis one of the land tenure problem in urban and rural areas of Indonesia. Conflicts that occurred came from the capitalism that has entered in various regions with the aim to gain benefits both individually and in groups. This study is to looks at the chronology of the conflict, the actors and the type of people political movements of their lands that have been excluded from theydaily livelihood resources. Partnership system built by PT. BBS (PT.BukitBintangSawit) resulted in changes to the access of land or agrarian resources. Land that originally as a source of community lifeÃ‚Â andexperienced a process of power transfer from community to company PT. Bukit BintangSawit.The research method is a comparative with expost facto approach. The data analysis was done in the form of literature study, resume result from Antoni and field result of year 2016 in order to understand the theory related to phenomenon. Data analysis is the view of experts who are studying the conflict on access theory purposed by Jess C. Ribot and Nancy Lee Peluso, while the conflict theory was using Fisher et.al. and theory of property rights from Schlager and Ostrom (1992). The results of the study indicate that the type of political movement performed the type of official politics and the conflict between local communities with PT BBS. Their movement is aim to reclaim their natural resources. Then the type of everyday politics related to the opposition openly to reject the operation of oil palm plantation companies in the area of Sago Village and ask for compensation related to the land they have seized. In addition, the actor in the case consists of three people who have economic capital, holders and makers and recognize property rights and government policy makers.